Culturalism and the "New" Poetry. A Poem by Pedro Gimferrer: "Cascabeles" from Arde el mar (1966) - Guillermo Carnero (Studies in 20th & 21st Century Literature, 1992)
The study deals with the group of Spanish poets commonly called the "novisimos" or "promocion de 1970," using as a base a poem by Pedro Gimferrer published in 1966. It studies the aesthetic break-through achieved by this generation, highlighting the concept of "culturalism" that critics used to define it twenty years ago. It examines the equivocal uses to which this concept can be put, and describes its correct meaning in the light of the aesthetic to which it refers. It then studies the mechanisms implicit in the writing of this non-confessional lyric poetry, centering it on two complementary procedures: the use of a historical persona that serves as an analogue ("personaje historico analogico"), and that of another work of art that functions as an objectifying device ("obra de arte ajena objetivadora"). It considers these in the light of two perspectives: the overcoming of neo-romantic rhetoric, and the participation of the reader.
Keywords: Spanish poets; poetry; novismos; promocion de 1970; Pedro Gimferrer; aestheticism; culturalism; historical persona; persona; personaje historico analogico; obra de arte ajena ojetivadora; neoromantic theory